2003
DOI: 10.1186/1472-6874-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian antibodies as detected by indirect immunofluorescence are unreliable in the diagnosis of autoimmune premature ovarian failure: a controlled evaluation

Abstract: Background: Ovarian antibodies as detected by indirect immunofluorescence have been used to detect ovarian autoimmunity, but to our knowledge the rate of false positive findings using this method has never been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 28 publications
(23 reference statements)
1
53
2
1
Order By: Relevance
“…However, there was no specificity and it varied according to source of ovarian tissue and maturation state. Novosad et al (2003) reported poor specificity with a commercially available kit which tested positive in nearly one-third of normally menstruating women [12]. The group thus affirmed that IIF is not a reliable tool to detect AOA.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, there was no specificity and it varied according to source of ovarian tissue and maturation state. Novosad et al (2003) reported poor specificity with a commercially available kit which tested positive in nearly one-third of normally menstruating women [12]. The group thus affirmed that IIF is not a reliable tool to detect AOA.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, it is essential to assess the presence of serum AOA when a woman first presents herself with infertility to the clinician. Specificity of AOA testing has been questioned and the available tests reported in literature have been challenged [12] due to high rates of false positives seen using sera from normal fertile controls. This problem of non-specificity has been overcome in a specific, simple and non-invasive diagnostic test developed by us [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian antibodies lack specificity, and testing for them is not warranted. 21 Pelvic ultrasonography identifies cases involving enlarged, multifollicular ovaries, which may undergo torsion, such as in isolated 17,20-lyase deficiency or autoimmune oophoritis (Table 2). An ovarian biopsy does not provide information that is helpful in the management of primary ovarian insufficiency and is therefore not indicated; pregnancy may occur even after examination of a biopsy specimen has shown that follicles are absent.…”
Section: Discussionmentioning
confidence: 99%
“…O valor preditivo do teste disponível no mercado é pobre como um método para identificar as mulheres com FOP. Num estudo de 26 mulheres com FOP e 26 mulheres com ciclos normais, 50% das mulheres com FOP e 31% de mulheres normais tinham anticorpos antiovarianos (27).…”
Section: Autoanticorpos Circulantesunclassified